The influence of Tiktok influencer exposure on food product purchase intention: The mediating role of materialism and moderating effect of FOMO among Generation Z in Padang City - Hummi Kalsum Bahri; Dwita, Vidyarini (Marketing Management Studies, 2025)
The objective of this research is to examine the impact of Exposure to Influencers on TikTok on the intention to purchase food products, with materialism as a mediator and Fear of Missing Out (FOMO) as a moderator among Generation Z in Padang City. Data was collected through an online questionnaire distributed to 142 respondents. The research employed a quantitative method with data analysis using Smart PLS and a bootstrap technique. The results reveal that (1) exposure to influencers has a significant effect on materialism, (2) exposure to influencers also significantly impacts the intention to purchase, (3) materialism significantly affects the intention to purchase, (4) FOMO does not moderate the relationship between exposure to influencers and purchase intention, and (5) materialism acts as a mediator in the relationship between exposure to influencers and purchase intention. These findings provide insights into how TikTok influencers affect consumer behavior and highlight the role of materialism in this process, while showing that FOMO does not play a significant moderating role